Relevansi Pemikiran Filosofis Ki Hadjar Dewantara Terhadap Sistem Pendidikan Hindu - Gede Agus Siswadi (Jurnal Pendidikan Agama, 2021)
This article seeks to examine the thoughts of Ki Hadjar Dewantara who is the father of national education. With the concept of education through the "Tricenter of Education" including family, school and community. In addition, the concept of "Trilogy" that he conveyed was about ing ngarso sung tulada, ing madya mangun karsa and tut wuri handayani. The method used in this study is a qualitative descriptive method by observing reading sources. The results of this study explain the basis of Ki Hadjar Dewantara's education and teaching sourced from his five dharmas. These basics are: (1) humanity, (2) the nature of life, (3) nationality, (4) culture, and (5) independence/freedom. The learning method promoted by Ki Hadjar Dewantara is the among method. Among has the meaning of maintaining the inner survival of students by accompanying and directing. Not only allowing the inner development of students but also keeping the inner state of students in good condition. The concept of education presented by Ki Hadjar Dewantara has relevance to the concept of education contained in Hinduism such as the level of education for children, the concept of aguron-guron, educating children's character and texts in the Vedic scriptures that explain the Hindu education system.